The Impossibility of ‘Good Mothering’ in Child Welfare Systems When Referred for Non-Traditional Harms - Nikki Rutter; Carlene Firmin; Donna Garvey; Kate O’Brien; Rachael Owens (Social Sciences)
Due to harmful narratives within child welfare and child protection services and systems, mothers in contact with these services who aim to meet the symbolic representation of the ‘ideal mother’ frequently find themselves being portrayed as the ‘bad mother’, even when their referral is ‘non-traditional’ (i.e., not specifically due to their perceived harmful actions or inactions). Through ‘ideal mother’ symbolism and narratives, there is disenfranchisement of service-engaged mothers; they are mistreated by services, which is normalised by wider discourses around motherhood. Mothers within these child welfare systems consistently experience judgement, the problematising of their parenting practices, and disempowerment despite not being the direct cause of harm to their children. This creates a sense of shame and makes the injustice of mothers’ experiences within child welfare systems invisible. This is a conceptual paper combining data generated from previously published work and a lived experience example (work with young mothers; mothers in contact with the criminal justice system; mothers with children who cause harm; and those with children experiencing extra-familial harm) using qualitative, participatory, and action-based approaches, and through emancipatory interview processes, disenfranchised mothers described their contact with child welfare and child protection systems as a source of structural, political, and/or societal injustice. Thus, such qualitative emancipatory work provides ways to acknowledge mothers in contact with child welfare services due to non-traditional harms, as they are a disadvantaged group who are too often disempowered to action change. Thus, we argue that participatory and action-based research should be a preferred method of exploring mothers’ experiences of child welfare systems, opening routes for reforming, as well as understanding systematic potential of services as oppressive and problematising rather than supportive and empowering.